INCREASING STUDENTS' DISASTER LITERACY THROUGH THE DISASTER MITIGATION CARD GAME (CAMIBEE) - Huda, Putriani Chayati; Rahmawati, Wulan; Khoeri, Ahmad Yusron; Nur Hayati, Muriani (Journal of Social Comunity Services, 2024)
General background: Disaster literacy is crucial in equipping students with knowledge and preparedness for disaster risk reduction. Specific background: Previous educational approaches to disaster mitigation often lack engaging and interactive methods, which may reduce students' motivation to learn about disaster preparedness. Knowledge gap: Despite the significance of disaster education, there is a need for innovative approaches that effectively convey disaster mitigation concepts in a way that captivates students' interest. Aims: This community service program aims to enhance disaster literacy through the implementation of a disaster mitigation card game, "Camibee," an adaptation of the Monopoly game, which encourages active learning and critical thinking among high school students. Results: The program demonstrated that the game-based learning method, particularly using the Camibee card game, significantly increased student engagement and understanding of disaster mitigation concepts. Students were enthusiastic, which translated into improved motivation to learn about disaster risk reduction. Novelty: This study presents a novel approach by integrating a competitive, enjoyable board game with educational content on disaster mitigation, providing an alternative to traditional disaster literacy education. Implications: The program contributes to the development of effective disaster education strategies that not only enhance students' disaster preparedness but also foster active participation and awareness. The findings suggest that this game-based approach could be widely applied in disaster education to improve literacy and preparedness in schools, empowering students to become agents of change in disaster risk management.